Characterization of swallow modulation in response to bolus volume in healthy subjects accounting for catheter diameter. (31st August 2017) - Ferris, Lara; Schar, Mistyka; McCall, Lisa; Doeltgen, Sebastian; Scholten, Ingrid; Rommel, Nathalie; Cock, Charles; Omari, Taher
Abstract : Objectives/Hypothesis: Characterization of the pharyngeal swallow response to volume challenges is important for swallowing function assessment. The diameter of the pressure‐impedance recording catheter may influence these results. In this study, we captured key physiological swallow measures in response to bolus volume utilizing recordings acquired by two catheters of different diameter. Study Design: Ten healthy adults underwent repeat investigations with 8‐ and 10‐Fr catheters. Liquid bolus swallows of volumes 2.5, 5, 10, 20, and 30 mL were recorded. Measures indicative of distension, contractility, and flow timing were assessed. Methods: Pressure‐impedance recordings with pressure‐flow analysis were used to capture key distension, contractility, and pressure‐flow timing parameters. Results: Larger bolus volumes increased upper esophageal sphincter distension diameter ( P < .001) and distension pressures within the hypopharynx and upper esophageal sphincter ( P < .05). Bolus flow timing measures were longer, particularly latency of bolus propulsion ahead of the pharyngeal stripping wave ( P < .001). Use of a larger‐diameter catheter produced higher occlusive pressures, namely upper esophageal sphincter basal pressure ( P < .005) and upper esophageal sphincter postdeglutitive pressure peak ( P < .001). Conclusions: The bolus volume swallowed changed measurements indicative of distension pressure, luminal diameter, and pressure‐flow timing; this is physiologically consistent with swallow modulation to accommodate larger, faster‐flowing boluses. Additionally, catheter diameter predominantly affects lumen occlusive pressures. Appropriate physiological interpretation of the pressure‐impedance recordings of pharyngeal swallowing requires consideration of the effects of volume and catheter diameter. Level of Evidence: NA. Laryngoscope, 128:1328–1334, 2018